2006
DOI: 10.1002/hep.21189
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of adefovir resistance in patients with lamivudine‐resistant chronic hepatitis B after 48 weeks of adefovir dipivoxil monotherapy†

Abstract: Although adefovir dipivoxil (ADV) has a unique profile of delayed and infrequent resistance in treatment-naïve chronic hepatitis B patients, the association of ADV resistance with previous lamivudine (LAM) resistance is not well understood. We compared the emergence of the ADV-resistant mutations rtA181V/T and rtN236T between LAM-resistant patients and treatment-naïve patients at 48 weeks of ADV monotherapy. Fifty-seven LAM-resistant patients and 38 treatment-naïve patients were treated with 10 mg/d ADV for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
233
5
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(262 citation statements)
references
References 31 publications
16
233
5
8
Order By: Relevance
“…While early studies of patients with lamivudine-resistant HBV suggested that switching to adefovir was efficacious, subsequent work demonstrated the rapid emergence of adefovir resistance in this patient population [42][43][44]. The emergence of adefovir resistance in this setting can be associated with viral rebound and hepatic decompensation [45].…”
Section: Discussionmentioning
confidence: 99%
“…While early studies of patients with lamivudine-resistant HBV suggested that switching to adefovir was efficacious, subsequent work demonstrated the rapid emergence of adefovir resistance in this patient population [42][43][44]. The emergence of adefovir resistance in this setting can be associated with viral rebound and hepatic decompensation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Genotypical analysis for ETV resistance was performed on a subset of patients showing virological breakthrough during follow-up using restriction fragment mass polymorphism analysis as previously described. 9 For restriction fragment mass polymorphism genotyping, viral DNA was amplified using PCR. Table 1 shows the sequences of forward and reverse primers used for PCR.…”
Section: Methodsmentioning
confidence: 99%
“…8 Sequential resistance to LAM and later ADV has been reported in patients who were switched to ADV monotherapy for LAM-resistant HBV. 9,10 Furthermore, ADV mutations emerged more commonly in LAM-resistant patients than in treatment-naïve patients. 9, 10 It was suggested that se-quential antiviral therapy leads to selection of multidrugresistant HBV, and evolution of mutations during continued treatment may select for mutants with increased replication fitness or maximal viral resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Adefovir resistance mutations are much more common in patients who have previously received lamivudine therapy. 18 HBV infection is a heavy health burden in China. National surveys found that the prevalence of HBV was 9.8% in 1992 and 7.2% in 2006 among the population aged 1-59 years.…”
Section: Introductionmentioning
confidence: 99%